Renal Dysfunction is a Risk Factor of Death after Gastric Endoscopic Submucosal Dissection in Elderly Patients Aged ≥80 Years - Kenichiro Okimoto; Makoto Arai; Hideaki Ishigami; Takashi Taida; Keiko Saito; Daisuke Maruoka; Tomoaki Matsumura; Tomoo Nakagawa; Tatsuro Katsuno; Naoya Kato (Canadian Journal of Gastroenterology and Hepatology, 2019)
Introduction. Endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) is well accepted. However, its adaptation for elderly patients is unclear. This study aimed to investigate the prognosis and long-term outcomes of ESD for EGC in elderly patients aged ≥80 years by comparing their findings to the findings of patients aged <80 years. Materials and Methods. The study included 533 patients (632 lesions). The patients were divided into an elderly group (age, ≥80 years; 108 patients; 128 lesions; mean age, 83.4 ± 2.7 years) and a nonelderly group (age, <80 years; 425 patients; 504 lesions; mean age, 69.6 ± 7.9 years). We compared patient and lesion characteristics, overall survival (OS), and disease-specific survival (DSS) between the 2 groups retrospectively. Multivariate analysis was performed to clarify the risk factors of death after ESD. Results. The rate of curative resection and adverse events was not significantly different between the groups. The mean survival time periods with regard to OS/DSS in the elderly and nonelderly groups were 75.8 ± 5.9 and 122.8 ± 2.6 months (P<0.05)/120.0 ± 3.0 and 136.4 ± 0.6 months (not significant), respectively. In the elderly group, eGFR <30 ml/min/1.73 m2 was an independent risk factor of death (hazard ratio = 5.32; 95% confidence interval = 1.39–20.5; P=0.015). Conclusion. ESD for EGC can be performed safely and can achieve high curability with good prognosis in elderly patients aged ≥80 years. After ESD, close attention should be paid to elderly patients with severe chronic kidney disease.